Prevalence and antibiotic susceptibility of clinical staphylococcus aureus isolates in various specimens collected from a tertiary care hospital, Hayatabad, Peshawar, Pakistan.: Antibiotic susceptibility of clinical staphylococcus aureus isolates in various specimens - Rehman, Latif Ur; Afzal Khan, Amir; Afridi, Pashmina; Ur Rehman, Sadeeq; Wajahat , Muhammad; Khan, Furqan (Pakistan Journal of Health Sciences, 2022)
Staphylococcus aureus is a notorious Gram-positive, non-spore-forming, opportunistic bacterium that causes a variety of infections including bacteremia, endocarditis, pneumonia, skin and soft tissue infections, and several others. Also, the overuse and misuse of drugs attributed to the crises of multidrug resistance especially in MRSA. Objective: Therefore, the aim of this study was to determine the prevalence rate of MRSA, antimicrobial susceptibility profiles of S. aureus, MRSA, and MSSA isolates to a variety of commonly used antibiotics, and its multidrug resistant patterns. Methods: Samples were collected from the microbiology department of HMC Peshawar, Pakistan. Antibiotic susceptibility patterns were determined under CLSI and EUCAST guideline, 2021 by following the Kirby-Bauer disc diffusion method. Results: Out of 106 S. aureus clinical isolates, 83 (78.3%) isolates were identified as MRSA and 23 (21.7%) were MSSA. In MRSA high resistance was exhibited to Penicillin G and cefoxitin (100%), followed by erythromycin 84.34% and ciprofloxacin 79.52%. Meanwhile low resistance was observed to doxycycline 19.28% followed by chloramphenicol 14.46%, teicoplanin and linezolid 2.41% for each respectively. High sensitivity in MRSA isolates was exhibited to linezolid 97.59% followed by teicoplanin 95.18%, chloramphenicol 85.54%, doxycycline 80.72% and fusidic acid 74.70%. A total of n=94 (88.67%) isolates were characterized as MDR. Conclusions: In conclusion, the most effective antibiotics used to treat S. aureus infections were linezolid, teicoplanin, chloramphenicol, doxycycline, fusidic acid, and gentamycin. In addition, the current study also noticed a significant prevalence of resistance to several antibiotics, emphasizing the importance of antibiotic usage monitoring.